2019
DOI: 10.1002/jia2.25290
|View full text |Cite
|
Sign up to set email alerts
|

Low detectable postpartum viral load is associated with HIV transmission in Malawi's prevention of mother‐to‐child transmission programme

Abstract: Introduction In 2011, Malawi implemented “Option B+,” a test‐and‐treat strategy for the prevention of maternal to child transmission of HIV (PMTCT); however limited data on viral load (VL) suppression exist. We describe VL suppression in HIV‐infected women at four to twenty‐six weeks postpartum, factors associated with VL suppression and the impact of VL suppression levels on MTCT. Methods HIV‐positive mothers at four to twenty‐six weeks postpartum were enrolled in a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 20 publications
3
43
2
Order By: Relevance
“…However, the possibility of viral load influencing the transmission risk should be of concern. Published studies have demonstrated a positive relationship between the viral load of some viruses and their ability to spread from mother to child [12,13]; it is still unclear whether SARS-CoV-2 has similar characteristics. In this case, we cannot estimate the mother's highest viral load before delivery, because she received the initial test on 6d of symptom onset, already after viral load reached the peak at 3 to 5d [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…However, the possibility of viral load influencing the transmission risk should be of concern. Published studies have demonstrated a positive relationship between the viral load of some viruses and their ability to spread from mother to child [12,13]; it is still unclear whether SARS-CoV-2 has similar characteristics. In this case, we cannot estimate the mother's highest viral load before delivery, because she received the initial test on 6d of symptom onset, already after viral load reached the peak at 3 to 5d [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…However, despite comparatively higher rates of durable VLS over 24 months in this cohort, approximately 1 in 5 women still experienced at least one post-partum episode of viremia which likely has implications for MTCT, as well as the health of the mothers. While we cannot specifically comment on the duration or frequency of viremic episodes in relationship to individual level MTCT (as both were measured at yearly intervals over 24 months), we previously showed that non-suppressed VL, including low-level viremia (>40–1000 copies/ml) measured in the early post-partum period was predictive of MTCT at enrolment (4–26 weeks) in this same cohort of women [ 13 ]. Further, in Zimbabwe, a similar PMTCT program using a universal test and treat strategy linked non-durable VLS to increased MTCT risk to 18 months [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…specifically comment on the duration or frequency of viremic episodes in relationship to individual level MTCT (as both were measured at yearly intervals over 24 months), we previously showed that non-suppressed VL, including low-level viremia (>40-1000 copies/ml) measured in the early post-partum period was predictive of MTCT at enrolment (4-26 weeks) in this same cohort of women [13]. Further, in Zimbabwe, a similar PMTCT program using a universal test and treat strategy linked non-durable VLS to increased MTCT risk to 18 months [8].…”
Section: Plos Onementioning
confidence: 97%
See 2 more Smart Citations